2011
DOI: 10.1007/s11240-011-0022-8
|View full text |Cite
|
Sign up to set email alerts
|

An in vitro system to study cyclopeptide heterophyllin B biosynthesis in the medicinal plant Pseudostellaria heterophylla

Abstract: Plant cyclopeptides are a large group of small molecule metabolites found in a wide variety of plants, including traditional Chinese medicinal plants. Many of the cyclopeptides have highly unusual structures and potent biological activities. However, the majority of the cyclopeptides have not been studied for their biosynthetic mechanisms. In this study, we have established a culture system for the biosynthetic study of heterophyllin B (HB), a cyclopeptide produced by the medicinal plant Pseudostellaria hetero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 24 publications
0
6
1
Order By: Relevance
“…Most interestingly, prePhHB contained a core peptide (IFGGLPPP) motif. However, this is different from previous reports that the core peptide of HB may be GGLPPPIF (Xu et al, 2012). In this study, we identified, cloned, and characterized the prePhHB from the tuberous root of P. heterophylla via RNA-seq database and the RACE method.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Most interestingly, prePhHB contained a core peptide (IFGGLPPP) motif. However, this is different from previous reports that the core peptide of HB may be GGLPPPIF (Xu et al, 2012). In this study, we identified, cloned, and characterized the prePhHB from the tuberous root of P. heterophylla via RNA-seq database and the RACE method.…”
Section: Discussioncontrasting
confidence: 99%
“…In addition, CP compounds can form tubular structures and act as membrane ion transferring carriers (Rodriguez-Vazquez et al, 2014). Plant CPs are a large group of small molecule metabolites, typically with 2–37 protein and non-protein amino acids (mainly L-amino acids), which are formed mainly by the peptidic bonds and isolated from the stem barks, leaves, seeds, and roots of a wide variety of higher plants (Condie et al, 2011; Xu et al, 2012). So far, more than 450 plant CPs have been discovered from 26 families of higher plants; they are most commonly found in the Caryophyllaceae , Rhamnaceae , and Violaceae families (Tan and Zhou, 2006; Burman et al, 2010; Pandey et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…SNAC mimics the enzyme-phosphopantetheine moiety that carries enzymatic intermediates in the cyclization enzyme reaction. However, non-enzymatic self-cyclization and non-reactiveness in SNAC derivatives have also been reported 52 53 . We synthesized N -acetoacetyl- L -Ile-SNAC as an intermediate of TeA biosynthesis to investigate the cyclization capability of the KS domain in TAS1; however, synthesized N -acetoacetyl- L -Ile-SNAC showed self-cyclization, the rate of which increased with increasing pH.…”
Section: Discussionmentioning
confidence: 99%
“…LPS, IFN-γ-induced RAW 264.7 macrophages and HEK-293-NF-κB luciferase stable cell lines were used to examine the effects of RAs on NO production and NF-κB signal pathway. RA-V (17) showed the best activities on NO production inhibition (IC 50 = 0.05 μM) and NF-κB signal pathway inhibition (IC 50 = 0.03 μM). [10] Tan and coworkers reported the quantitative structure-activity relationship (QSAR) analysis of 54 RAs.…”
Section: Discovery Of New Cytotoxic Rasmentioning
confidence: 99%